KARAKTER WIRAUSAHA PADA MAHASISWA PROGRAM STUDI D4 MANAJEMEN PERHOTELAN UNIVERSITAS NEGERI PADANG - Martalena, Martalena; Silfeni, Silfeni; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the entrepreneurship character ofHotel Management at State University of Padang (UNP). This research consistssixth of indicators which is: confident, task-oriented and results, dare to take arisk, leadership, originality and future-oriented. This type of research isdescriptive research with quantitative data. Population in this research amount567 people. Data retrieval technique is probability sampling which isproportionate stratified random sampling. The total of sample in this research is85 people. Data collection using a questionnaire based on a Likert’s scale thattested for validity and reliability. Generally based on the results entrepreneurshipcharacter Hotel Management of UNP states that 4% respondent expressed verywell, 45% respondent said good, 50% of respondent states good enough and 1%respondent said not good and there is no respondent states very bad.Keywords: entrepreneurship character